2015
DOI: 10.1890/es14-00514.1
|View full text |Cite
|
Sign up to set email alerts
|

Carbon stable isotopes suggest that hippopotamus‐vectored nutrients subsidize aquatic consumers in an East African river

Abstract: The common hippopotamus, Hippopotamus amphibius, transports millions of tons of organic matter annually from its terrestrial feeding grounds into aquatic habitats. We evaluated whether carbon stable isotopes (δ13C) can be used as tracers for determining whether H. amphibius‐vectored allochthonous material is utilized by aquatic consumers. Two approaches were employed to make this determination: (1) lab‐based feeding trials where omnivorous river fish were fed a H. amphibius dung diet and (2) field sampling of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(48 citation statements)
references
References 29 publications
3
45
0
Order By: Relevance
“…In addition, Hoeinghaus, Winemiller, and Agostinho () found that for low gradient rivers, C3 macrophytes were the most important source contributors, followed by phytoplankton. The enriched POM samples from this river may be indicative of the high inputs from hippopotamus dung, which tend to be 15 N and 13 C enriched (Jackson et al., ; Masese et al., ; McCauley et al., ), and high in nutrients (Kilham, ; McLachlan, ). The fast turnover rates of phytoplankton (Setaro & Melack, ; Train & Rodrigues, ), generally a major constituent of POM (Bukaveckas et al., ) (most other submerged macrophytes were not similarly enriched in 15 N or 15 C), could indicate that the enriched position of POM was as a result of recent episodic 15 N and 15 C enrichment from hippopotamus dung.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Hoeinghaus, Winemiller, and Agostinho () found that for low gradient rivers, C3 macrophytes were the most important source contributors, followed by phytoplankton. The enriched POM samples from this river may be indicative of the high inputs from hippopotamus dung, which tend to be 15 N and 13 C enriched (Jackson et al., ; Masese et al., ; McCauley et al., ), and high in nutrients (Kilham, ; McLachlan, ). The fast turnover rates of phytoplankton (Setaro & Melack, ; Train & Rodrigues, ), generally a major constituent of POM (Bukaveckas et al., ) (most other submerged macrophytes were not similarly enriched in 15 N or 15 C), could indicate that the enriched position of POM was as a result of recent episodic 15 N and 15 C enrichment from hippopotamus dung.…”
Section: Discussionmentioning
confidence: 99%
“…By travelling further inland in response to lower donor ecosystem productivity, hippos spend a longer time feeding in the grasslands, which leads to less time spent in the river and therefore less excretion/egestion in the aquatic ecosystem (Subalusky et al, ). The magnitude of hippo inputs entering the recipient ecosystem appears to drive large differences in effects on ecosystem function, with low levels of input increasing primary and secondary production, and high levels decreasing production, particularly during low discharge when inputs concentrate on the river bottom (Masese et al, , ; McCauley et al, ; Dawson et al, ; Stears et al, ; Dutton et al, ; Subalusky et al, ). Hippo inputs can become so concentrated they lead to hypoxic conditions in the hippo pools and hypoxic floods and fish kills downstream, a condition Dutton et al .…”
Section: The Effects Of Subsidy Characteristics On Trophic Dynamics Amentioning
confidence: 99%
“…Daily contribution of Hippopotamus amphibius population to Mara River were estimated up to 8,563 kg dry matter, 3,499 kg C, 48 kg P and 492 kg N [26]. And these nutrient subsidies were beneficial to aquatic invertebrate and fish [104]. In addition, some small mammals themselves can be terrestrial subsidies for aquatic consumers.…”
Section: Impacts Of Aquatic Resource Subsidies On Specific Terrestriamentioning
confidence: 99%